2014
DOI: 10.1111/ppe.12125
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prepregnancy Body Mass Index and Risk of Spontaneous Preterm Birth

Abstract: Background: Findings from studies examining risk of preterm birth associated with elevated prepregnancy body mass index (BMI) have been inconsistent. Methods: Within a large population-based cohort, we explored associations between prepregnancy BMI and spontaneous preterm birth across a spectrum of BMI, gestational age, and racial/ethnic categories. We analysed data for 989 687 singleton births in California, 2007-09. Preterm birth was grouped as 20-23, 24-27, 28-31, or 32-36 weeks gestation (compared with 37-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
88
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 31 publications
17
88
3
8
Order By: Relevance
“…Our finding of increased risk of spontaneous preterm delivery at 23–27 weeks among obese nulliparous women is similar to a previous large California study, 31 based on birth records linked with hospital discharge data that excluded chronic as well as gestational hypertension and diabetes and stratified by parity, and another Swedish study 21 based on birth registry that included women with chronic diseases. Shaw et al 31 also reported an inverse association between excess prepregnancy BMI and the risk of spontaneous moderate to late preterm delivery which is similar to our results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding of increased risk of spontaneous preterm delivery at 23–27 weeks among obese nulliparous women is similar to a previous large California study, 31 based on birth records linked with hospital discharge data that excluded chronic as well as gestational hypertension and diabetes and stratified by parity, and another Swedish study 21 based on birth registry that included women with chronic diseases. Shaw et al 31 also reported an inverse association between excess prepregnancy BMI and the risk of spontaneous moderate to late preterm delivery which is similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…11, 12, 31 Among studies which reported overall risk of spontaneous preterm deliveries in association with prepregnancy obesity, some reported null associations, 30 or an increased overall risk among obese women, 21, 23 whereas others reported a decreased risk. 11, 25, 29 Difference in preterm delivery incidence, case classification, racial composition, and study design could partly explain these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of nearly 1 million singleton births in California between 2007 and 2009, maternal obesity was associated with a significantly increased risk for spontaneous PTB at 20 to 23 weeks and 24 to 27 weeks across all racial/ethnic groups. 6 Obesity was not consistently associated with later PTB, however.…”
Section: Pregnancy Durationmentioning
confidence: 94%
“…Recent epidemiological studies also suggest that derangements in glucose and fatty acid metabolism may drive such pregnancy complications. For example, maternal gestational diabetes mellitus (GDM) and obesity are independently, and additively, associated with increased rates of PE (Catalano et al 2012) as well as spontaneous preterm birth (Shaw et al 2014). There may be shared mechanisms contributing to PE and preterm labor (PTL) pathogenesis (see below).…”
Section: Placental Metabolismmentioning
confidence: 98%